ANALISIS PERUBAHAN KOMODITAS PERTANIAN TANAMAN KELAPA SAWIT DI KECAMATAN KAPUR IX KABUPATEN LIMA PULUH KOTA - M. Abeng Tohari; Dedi Hermon (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Oil palm is a plantation commodity that has grown rapidly in Kapur IX District, Lima Puluh Kota Regency. This growth is characterized by plantation expansion, resulting in land cover changes and increased agricultural production. This study aims to analyze land cover changes into oil palm plantations between 2014 and 2024 and to examine the development of oil palm production and productivity during 2014–2024. This study employed a quantitative approach supported by spatial analysis. Landsat imagery from 2014 and 2024 was analyzed using land cover classification and overlay techniques, while production and productivity data were analyzed descriptively. Mapping accuracy was assessed using overall accuracy and the Kappa coefficient. The results show that oil palm plantation area increased from 1,150.00 ha to 25,800.00 ha, representing a growth of 2,143.48%. The expansion mainly originated from forest conversion, with forest area declining from 69,162 ha to 37,898 ha. Overlay analysis revealed that 95.88% of the 2024 oil palm plantations were converted from non-oil palm land. The classification achieved an overall accuracy of 90.00% and a Kappa coefficient of 0.8455. Oil palm production increased from 862.50 tons to 58,566.00 tons (6,689.68%), while productivity rose from 0.75 tons/ha to 2.27 tons/ha. These findings indicate that oil palm expansion contributes to agricultural production growth but requires sustainable management to balance economic benefits and environmental conservation.